Factors associated with continued participation in a matched monetary incentive programme at local farmers' markets in low-income neighbourhoods in San Diego, California. Issue 15 (31st July 2017) - Ratigan, Amanda R; Lindsay, Suzanne; Lemus, Hector; Chambers, Christina D; Anderson, Cheryl AM; Cronan, Terry A; Browner, Deirdre K; Wooten, Wilma J
Abstract: Objective: The Farmers' Market Fresh Fund Incentive Program is a policy, systems and environmental intervention to improve access to fresh produce for participants on governmental assistance in the USA. The current study examined factors associated with ongoing participation in this matched monetary incentive programme. Design: Relationship of baseline factors with number of Fresh Fund visits was assessed using Poisson regression. Mixed-effects modelling was used to explore changes in consumption of fruits and vegetables and diet quality. Setting: San Diego, California. Subjects: Recipients of Supplemental Nutrition Assistance Program (SNAP), Special Supplemental Nutrition Program for Women, Infants, and Children (WIC) and Supplemental Security Income (SSI) who attended participating farmers' markets from 2010 to 2012 ( n 7298). Results: Among those with participation for ≤6 months, factors associated with increased visits included reporting more daily servings of fruits and vegetables (F&V) at baseline, being Vietnamese or Asian/Pacific Islander, and eligibility because of SNAP/CalFresh or SSI ( v . WIC). Among those who came for 6–12 months, being Asian/Pacific Islander, eligibility because of SNAP/CalFresh and enrolling in the autumn, winter or spring were associated with a greater number of Fresh Fund visits. Among those who came for >12 months, being male and eligibility because of SSI were associated with a greater number of visits. Overall, the odds of increasing number of servings of F&V consumed increased by 2 % per month, and the odds of improved perception of diet quality increased by 10 % per month. Conclusions: Sustaining and increasing Fresh Fund-type programme operations should be a top priority for future policy decisions concerning farmers' market use in low-income neighbourhoods.